Penguatan Self-Confidence dan Motorik Anak Down Syndrome Melalui Seni Drama dan Tari - Abdullah, Meutiah Mutmainnah; Sahira, Nur Apika; Warahmah, Mawaddah; Faizah, Nur; Aboe Kasim, Siti Rahma Indriani; Amelia, Restu Ananda (Jurnal Abdimas Kesehatan (JAK), 2025)
Children with down syndrome experience cognitive development limitations and genetic abnormalities. Although children with down syndrome have limitations, with appropriate guidance and support, they can grow into independent and productive individuals within their communities. The partner in this community service program is SLB YPAC Makassar, with the target of 10 children with down syndrome. The program aims to strengthen their self-confidence and motoric skills as part of the empowerment efforts. The method applied is the art of drama and dance which is implemented in six stages. The stages of the program include dialogue training, role playing, and dance movements. To measure self-confidence and motor skills, an observation checklist was used. The results showed a significant improvements in the children with down syndrome in dialogue, body movement coordination, and participation in drama and dance performances attended by parents, teachers, and friends indicating increase trend in 70% of self-confidence and 80% of motoric skills. The program proved effective in strengthening these two aspects in children with down syndrome. Therefore, to ensure its sustainability, a drama and dance arts community has been established at SLB YPAC Makassar.